Performance evaluation of mud crab fishing gears in Chilika lake - Mohapatra, Anil; Mohanty, Rajeeb K; Mohanty, S K (Indian Journal of Fisheries, 2012)
The annual catch per unit effort, (CPUE) values for nine different types of fishing gears in use in mud crab fishery in Chilika lake, Odisha were estimated to evaluate their comparative catching performance. The pooled mean annual CPUE values indicated that the lift net was the most efficient crab fishing gear (0.78 + 0.04), followed by crab pot (0.61 + 0.06) and baited long line without hooks (0.53+0.03). Monofilament gill net (0.44 ± 0.02), single hook hand line (0.37 ± 0.016), monofilament screen barrier (0.34 ± 0.02) and triangular push net (0.29 ± 0.02) showed moderate fishing efficiency, while split bamboo traps (0.19 ± 0.01) and scoop net (0.10 ± 0.006) were the least efficient gears. The results of the present study also indicate the need for regulation of crab fishing gears such as monofilament screen barrier trap and triangular push net, in which the catch of juvenile fishes, prawns and crabs predominate, in order to conserve fishery resources in the Chilika lake